Prevalence of vitamin D3 deficiency in patients with type 2 diabetes and proteinuria - Stojšić-Vuksanović Tatjana; Knežević Violeta (Vojnosanitetski Pregled)
Background/Aim. Vitamin D3 plays an important role in glucose metabolism, with influence on insulin secretion and sensitivity. Low grade inflammation is present in patients with diabetes type 2 and it is a known fact that vitamin D has an anti-inflammatory effect. Vitamin D deficiency is particularly pronounced in patients with diabetic nephropathy. Vitamin D3 levels during the year are associated with seasonal changes primarily influenced by UV radiation. The aim of the study was to examine the prevalence of vitamin D3 deficiency in patients with diabetic nephropathy. Methods. Patients with type 2 diabetes and diabetic nephropathy were included in the study after the vitamin D3 levels were established. The results were classified according to a lower limit level given for each month being reduced or normal values. For the purpose of further research, patients with low vitamin D3 levels were divided into two groups, study and control group, each including 45 patients. The study group received cholecalciferol at the dose necessary to achieve the intended optimal vitamin D3 blood level of 90–100 nmol/L. Results. At the beginning of the study, vitamin D3 value for all patients with vitamin D3 deficiency (n = 90) was 45.1 ± 15.6 nmol /L. Vitamin D3 deficiency in the study sample (n = 109) was found in 82.56% of participants, while the normal values of vitamin D 3 were found in 1 7.43% of patients. There is a statistically significant difference in the deviation of vitamin D3 levels from the lower normal values in the whole group of subjects between winter and summer, with the deviation being more pronounced in summer. There is no gender difference in these values, although in both men and women there is a more pronounced deviation in summer. Conclusion. Vitamin D3 deficiency is significantly represented in patients with type 2 diabetes and diabetic nephropathy.